Teorias e Doutrinas Sociais contemporâneas - Berutti A. Moreira, Hilton; Rego Costa, J. M.; Manso da Costa Reis, W. L.; Gonçalves da Motta, Omar; Pessoa da Silveira, Mário (A Defesa Nacional, 2021)
A Democracia.